A qualitative study exploring midlife women's stages of change from domestic violence towards freedom. Issue 1 (December 2016) - Keeling, June; Smith, Debbie; Fisher, Colleen
Abstract Background Domestic Violence (DV) remains a significant global health problem for women in contemporary society. Existing literature on midlife women's experiences of domestic violence is limited and focuses on health implications. Leaving a violent relationship is a dynamic process that often requires multiple attempts and separations prior to final termination. The aim of this study was to explore the process of leaving a violent relationship for midlife women. Methods This qualitative study involved fifteen women aged between 40–55 who had accessed residential and non-residential community support services for domestic violence within the UK. Community-based support agencies provided these women with access to letters of invitation and participant information sheet explaining the study. The women notified agency staff who contacted the research team to arrange a mutually convenient time to meet within a safe place for both the women and researchers. It was stressed to all potential participants that no identifiable information would be shared with the agency staff. Women were considered survivors of DV if they defined themselves as such. Data were gathered through semi structured interviews, transcribed verbatim and thematically analysed. Results Midlife women appear to differ from younger women by transitioning quickly though the stages of change, moving rapidly through the breaking free onto the maintenance stage. This rapid transition is the resultant effect of living with long-term violence causing a shift in the women's perception towards the violent partner, with an associated reclamation of power from within the violent relationship. A realisation that rapid departure from the violence may be critical in terms of personal safety, and the realisation that there was something 'wrong' within the relationship, a 'day of dawning' that had not been apparent previously appears to positively affect the trajectory of leaving. Conclusions Midlife women appeared to navigate through the stages of change in a rapid linear process, forging ahead and exiting the relationship with certainty and without considering options. Whilst these findings appear to differ from younger women's process of leaving, further research is needed to explore and understand the optimum time for intervention and support to maximise midlife women's opportunities to escape an abusive partner, before being reflected appropriately in policy and practice.